Pengaruh Penerapan Studi Kasus terhadap Pengetahuan Pelanggaran Kode Etik Profesi Bidang IT bagi Mahasiswa Otomasi Sistem Permesinan - Nur Asmi Rahmawati (Universitas Negeri Makassar, 2018)
This study was conducted to determine the effect of the application of case studies on knowledge of violations of the professional code of ethics in the IT field for students majoring in Mechanical Systems Automation. The research method used was an experiment with the design of